VOWELS AND THEIR MODIFICATION - Teshaboyeva Nafisa Zubaydullayevna,; Berdimurodova Dildora Qahramon qizi, (TADQIQOTLAR, 2026)
ANNOTATION: This article explores the nature of vowels and the ways in which they are modified in connected speech. It examines the articulatory and acoustic characteristics of vowels, focusing on how factors such as stress, intonation, speech rate, and phonetic environment influence vowel quality and quantity. Special attention is given to common types of vowel modification, including reduction, length variation, and assimilation. The article also highlights the significance of vowel modification in phonetics  and  phonology,  emphasizing  its  role  in  natural  speech,  pronunciation accuracy, and language teaching.